Diretrizes para o processo de projeto de edifícios hospitalares - Oliveira, Edgar Peixoto de (2010)
This paper aims to propose guidelines for the design process of hospital buildings. To achieve this objective, literature review and case studies were conducted in three architectural firms specializing in projects for hospital buildings. It was possible to see how management is performed in the design process in each of these companies and what are the difficulties and differences between the design process of hospital buildings and design process of other built environments. The Company 1 has been operating for 11 years developing architectural plans for the hospital and residential segments, which contributed to identifying the differences between the design processes of these two segments. The Company 2 has been operating for 3 years coordinating the design process of residential, hospital, shopping and hotels, bringing a vision of the management process. The Company 3 has extensive experience in developing architectural plans for the hospital segment, serving for 32 years exclusively in this segment. The observation of the work of these companies, together with the literature review served as a subsidy for the drafting of guidelines for the design process of hospital buildings, as a contribution to the quality of it.